The Tuberculosis of Female Genital Tract: About 5 Cases and Review of Literature - Ranaivomanana, Volahasina Francine; Andrianjafitrimo, Holy Tiana; Ranaivoson, Haingo Voahangy Rabetafika; Randrianjafisamindrakotroka, Nantenaina Soa (International Journal For Research In Biology & Pharmacy, 2021)
ABSTRACT Female genital tuberculosis is a rare condition, affecting mostly young women. It is mainly seen in developing countries. The aim of this study is to describe the epidemiological and pathological aspects of female genital tuberculosis.This is a retrospective and descriptive study of genital tuberculosis diagnosed in women, over a period of 5 years and half, from January 2014 to June 2019. We included the locations on the genital tract and excluded the other locations.We recruited 369 cases of extra-pulmonary tuberculosis and selected 5 cases of female genital location. The age of the patients ranged from 14 to 48 years, with an average of 28.8 years. The locations were cervical (2/5), uterine (2/5) and tubal (1/5). The morphological aspect was typical with epithelioid granulomas, Langhans giant cells with caseous necrosis in 2 cases, without caseous necrosis in 3 cases. In one of the cervical cases, there was associated with high-grade intraepithelial neoplasia. Female genital tuberculosis is a rare form of extra-pulmonary tuberculosis. The diagnosis is histological. The morphological aspect can sometimes pose differential diagnoses requiring a confrontation with the clinic or other specific examinations.